2018
DOI: 10.1007/s10826-018-1268-0
|View full text |Cite
|
Sign up to set email alerts
|

Family and Peer Influences on Substance Attitudes and Use among Juvenile Justice-Involved Youth

Abstract: Juvenile justice-involved youth experience high rates of substance use, which is concerning given associated negative consequences, including health and functional deficits. Family and peer factors are associated with a high risk of substance use among justice-involved youth. It is hypothesized that this risk process operates through pro-drug attitudes. However, limited research has been conducted on the mechanisms through which family and peer factors increase risk for substance use among juvenile justice inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 69 publications
(71 reference statements)
2
11
0
1
Order By: Relevance
“…Moreover, family members and peers drinking were associated with increased risk of youths’ alcohol use 4 , 23 , 28 , 29 . In particular, deviant peers on substance use have a strong influence on alcohol use for youths residing in more disordered neighborhoods through alcohol offers and share positive attitudes toward alcohol use 4 , 23 , 27 , 30 .…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, family members and peers drinking were associated with increased risk of youths’ alcohol use 4 , 23 , 28 , 29 . In particular, deviant peers on substance use have a strong influence on alcohol use for youths residing in more disordered neighborhoods through alcohol offers and share positive attitudes toward alcohol use 4 , 23 , 27 , 30 .…”
Section: Discussionmentioning
confidence: 98%
“…Th e behavior identifi ed as "Drug distribution only" is reserved for the members of sports fan groups. (Allen, Donohue, Griffi n, Ryan & Turner, 2003;Krosnick & Judd, 1982;Van Ryzin, Fosco & Dishion, 2012) and that they play a crucial role in deviant behavior of various nature. Th is research shows, however, that this is not quite the case.…”
Section: Discussionmentioning
confidence: 99%
“…Када се чита литература о утицајима вршњачких група на злоупотребу дроге, врло брзо се стекне утисак о снажним и непосредним утицајима тих група на ово понашање. Штавише, неки аутори су изричито тврдили да је у адолесценцији тај утицај најјачи, највећи, да се улога породице помера у правцу вршњачких група (Allen, Donohue, Griffi n, Ryan & Turner, 2003;Krosnick & Judd, 1982;Van Ryzin, Fosco & Dishion, 2012) и да оне имају пресудну улогу у девијантним понашањима разне природе. Ово истраживање показује, међутим, да то није баш тако.…”
Section: дискусијаunclassified
See 1 more Smart Citation
“…For instance, Anderberg and Dahlberg (2018) and Johnston, O'Malley, Miech, Bachman and Schulenberg (2015) found that substance abuse was higher among girls in early adolescence, while boys showed higher rates of abuse during late adolescence. Among the factors influencing drug use are peer and other social influences (Zapolski et al, 2019). The reasons for drug use among adolescent boys and girls can be to cope with mood changes, low self-esteem, or discomfort in social settings (Schwinn, Schinke, Hopkins, & Thom, 2016).…”
Section: Introductionmentioning
confidence: 99%